THE EFFECT OF LEARNING MOTIVATION ON LEARNING OUTCOMES THROUGH JIGSAW TYPE COOPERATIVE MODEL AT GRADE V SD RK BUDI LUHUR MEDAN - Sukly; Regina Sipayung; Ester J. Simarmata; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of learning motivation on learning outcomes through a jigsaw type cooperative model on Theme 8 at Grade V SD RK Budi Luhur Medan. The research method used was an experimental type of quantitative research. The data were obtained by using data collection tools in the form of documentation, a questionnaire of 25 statements and 33 questions. The research was conducted at grade V SD RK Budi Luhur Medan on 20 to 21 May 2021. The number of samples were 35 students selected by saturated sampling technique. Based on statistical analysis of the data, it was obtained that the results of learning motivation questionnaire with student enthusiasm were 48% in very high category and the results of the pretest were answered by students was an average value of 65.8 in moderate category. Furthermore, the results of the post test scores obtained by students from the answers was an average value of 86.74 with very good category. The results of the correlation analysis of the influence of learning motivation on learning outcomes through Jigsaw Cooperative model obtained a correlation value of rcount = 0.880 with rtable = 0.334. Thus, the value of rcount was higher than the value of rtable, so the correlation was very significant. Hypothesis testing with t-test obtained tcount = 10,618 ttable 1,697. It was concluded that there was a significant influence between learning motivation on learning outcomes through Jigsaw Cooperative Model.